Path Analysis on Gestational Socio-economic Determinants of Nutritional Status in Children Under Five in Purworejo Regency, Central Java - Ayuningrum, Ika Yuli; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2017)
Background: Undernutrition by height-for-age standard starts during pregnancy and continues to the first two years of life. Linear growth disorders among children under five years are associated with morbidity, mortality, loss of physical growth potential, reduced neurological development, reduced cognitive functions, and increased risks of adulthood chronic diseases. In 2015, the number of undernourished children under five (height-for-age) reached 156 million globally. Purworejo regency was an area with the second highest under